Factors critical to peacekeeping achieving stability: learning from the African Union’s peace operations - Cocodia, Jude (2016)
This thesis analyses the factors that determine the provision of stability in peacekeeping operations and the peacekeeping operations of the African Union (AU). It makes theoretical and empirical contributions, and supports the claim that the AU has been effective in peacekeeping.